Pengaruh Model Pembelajaran Student Facilitator And Explaining Terhadap Hasil Belajar Siswa Kelas V SD - Egry Winda Nababan; Ester Julinda Simarmata; Juliana Juliana; Reflina Sinaga; Nova Florentina Ambarwati; Henny Saida Florentina; Godlif Sianipar (Journal on Education, 2024)
This study aims to determine the effect of using the Student facilitator and explaining learning model on student learning outcomes on the theme 8 of our best friend's environment in class V of SD Negeri 173442 Batunagodang in the 2023/2024 learning year. In this study using quantitative methods, sampling using purposive samples and the sample used was class V which amounted to 30 students. The results of this study indicate that student learning outcomes using the Student facilitator and explaining model are included in the very good category with an average of 80.16 with a correlation test result of 0.815 which means rcount (0.815) ≥ rtabel (0.361) then Ha is accepted. So there is a strong influence between the use of the Student facilitator and explaining learning model on student learning outcomes on the theme of our best friend's environment in class V of SD Negeri 173442 Batunagodang. It can be seen from the results of the T-test research where tcount ≥ ttable, namely 7.432 ≥ 2.048 so it can be stated that Ha is accepted. This shows that there is a significant positive effect of using the Student facilitator and explaining learning model on student learning outcomes on the theme of our best friend's environment in class V of SD Negeri 173442 Batunagodang in the 2023/2024 learning year.